The Deacetylase SIRT1 Regulates the Replication Properties of Human Papillomavirus 16 E1 and E2 - Das, Dipon (J Virol, 2017)
Human papillomaviruses (HPV) replicate their genomes in differentiating epithelium using the viral proteins E1 and E2 in association with host proteins. While the roles of E1 and E2 in this process are understood, the host factors involved and how they interact with and regulate E1-E2 are not. Our previous work identified the host replication and repair factor TopBP1 as an E2 partner protein essential for optimal E1-E2 replication and for the viral life cycle. The role of TopBP1 in host DNA replication is regulated by the class III deacetylase SIRT1; activation of the DNA damage response prevents SIRT1 deacetylation of TopBP1, resulting in a switch from DNA replication to repair functions for this protein and cell cycle arrest. Others have demonstrated an essential role for SIRT1 in regulation of the HPV31 life cycle; here, we report that SIRT1 can directly regulate HPV16 E1-E2-mediated DNA replication. SIRT1 is part of the E1-E2 DNA replication complex and is recruited to the viral origin of replication in an E1-E2-dependent manner. CRISPR/Cas9 was used to generate C33a clones with undetectable SIRT1 expression and lack of SIRT1 elevated E1-E2 DNA replication, in part due to increased acetylation and stabilization of the E2 protein in the absence of SIRT1. The results demonstrate that SIRT1 is a member of, and can regulate, the HPV16 replication complex. We discuss the potential role of this protein in the viral life cycle. IMPORTANCE HPV are causative agents in a number of human diseases, and currently only the symptoms of these diseases are treated. To identify novel therapeutic approaches for combating these diseases, the viral life cycle must be understood in more detail. This report demonstrates that a cellular enzyme, SIRT1, is part of the HPV16 DNA replication complex and is brought to the viral genome by the viral proteins E1 and E2. Using gene editing technology (CRISPR/Cas9), the SIRT1 gene was removed from cervical cancer cells. The consequence of this was that viral replication was elevated, probably due to a stabilization of the viral replication factor E2. The overall results demonstrate that an enzyme with known inhibitors, SIRT1, plays an important role in controlling how HPV16 makes copies of itself. Targeting this enzyme could be a new therapeutic approach for combating HPV spread and disease.